BNT162b2 COVID-19 vaccination in children alters cytokine responses to heterologous pathogens and Toll-like receptor agonists - Noé, Andrés; Dang, Thanh D.; Axelrad, Christine; Burrell, Emma; Germano, Susie; Elia, Sonja; Burgner, David; Perrett, Kirsten P.; Curtis, Nigel; Messina, Nicole L. (Frontiers in Immunology, 2023)
Background: Vaccines can have beneficial off-target (heterologous) effects that alter immune responses to, and protect against, unrelated infections. The heterologous effects of COVID-19 vaccines have not been investigated in children. Aim: To investigate specific and heterologous immunological effects of BNT162b2 COVID-19 vaccination in children. Methods: A whole blood stimulation assay was used to investigate in vitro cytokine responses to heterologous stimulants (killed pathogens, Toll-like receptor ligands and SARS-CoV-2 antigens). Samples from 29 children, aged 5-11 years, before and 28 days after the second BNT162b2 vaccination were analysed (V2+28). Samples from eight children were analysed at six months after BNT162b2 vaccination. Results: At V2+28, interferon-γ and monocyte chemoattractant protein-1 responses to S. aureus, E. coli, L. monocytogenes, BCG vaccine, H. influenzae, hepatitis B antigen, poly(I:C) and R848 stimulations were decreased compared to pre-vaccination. For most of these heterologous stimulants, IL-6, IL-15 and IL-17 responses were also decreased. There were sustained decreases in cytokine responses to viral, but not bacterial, stimulants six months after BNT162b2 vaccination. Cytokine responses to stimulation with irradiated SARS-CoV-2, and spike glycoprotein subunits (S1 and S2) were increased at V2+28 for most cytokines and remained higher than pre-vaccination responses 6 months after BNT162b2 vaccination for irradiated SARS-CoV-2 and S1. There was no correlation between BNT162b2 vaccination-induced anti-receptor binding domain IgG antibody titre at V2+28 and cytokine responses. Conclusions: BNT162b2 vaccination in children alters cytokine responses to heterologous stimulants, particularly one month after vaccination. This study is the first to report the heterologous effects of COVID-19 vaccination in children.